RGBeat: A Recoloring Algorithm for Deutan and Protan Dichromats. - G. Ribeiro, M. Madalena; J. P. Gomes, Abel (International Journal of Interactive Multimedia and Artificial Intelligence, 2023)
Deutan and protan dichromats only see exactly two hues in the HSV color space, 240-blue (240o) and 60-yellow (60 o). Consequently, they see both reds and greens as yellows; therefore, they cannot distinguish reds from greens very well. Thus, their color space is 2D and results from the intersection between the HSV color cone and the 60º-240º plane. The RGBeat recoloring algorithm’s main contribution here is that it is the first recoloring algorithm that enhances the color perception of deutan and protan dichromats but without compromising the lifelong color perceptual learning. Also, as far as we know, this is the first HTML5-compliant web recoloring approach for dichromat people that considers both text and image recoloring in an integrated manner.